EKSPLORASI MINAT BACA RENDAH MASYARAKAT INDONESIA: PERSPEKTIF MULTIDISIPLIN: Exploring Low Reading Interest Among Indonesian Society: A Multidisciplinary Perspective - Seventilova, I Gusti Ngurah Octova (Yayasan Al-Amin Qalbu, 2024)
This research explores the multidimensional factors contributing to this phenomenon. Drawing upon insights from various disciplines including psychology, sociology, education, and cultural studies, this study provides a comprehensive understanding of the issue. Key findings indicate that individual factors such as reading habits, motivation, and cognitive development significantly influence reading interest. Moreover, social influences, including family, peer groups, and the education system, play a crucial role in shaping individuals' reading behaviors. External factors such as access to quality reading materials, economic challenges, and the pervasive influence of digital media further contribute to the low reading interest observed. Challenges in addressing low reading interest in Indonesia are multifaceted, requiring holistic and evidence-based interventions. Strategies to improve reading interest should involve collaboration among government agencies, educational institutions, communities, and the private sector. Concrete steps such as enhancing access to reading materials, promoting literacy culture at home and in schools, and developing balanced media literacy programs are essential in tackling the issue effectively